2x + 3y – z = 1 -----(1)
3x + y + 2z = 1 ----(2)
2x + 2y – 3z = –5 ----(3)
Multiply equation (1) by 2
4x+6y-2z=2
3x + y + 2z = 1 ----(2)
Add:
7x+7y = 3 ------(4)
Multiply equation (1) by -3
-6x-9y+3z = -3
2x + 2y- 3z = –5 ----(3)
Add:
-4x-7y=-8 ---(5)
Solve equations (4) and (5)
7x+7y = 3 ------(4)
-4x-7y=-8 ---(5)
Add:
3x= -5
x=-5/3 ----- x solved
plug x=-5/3 into equation (4)
7(-5/3) +7y = 3
-35/3 +7y = 3
-35+21y=9
21y=44
y=44/21 ---- y solved
substitute x=-5/3 & y = 44/21 into equation (1)
2(-5/3) + 3(44/21) -z = 1
-10/3+132/21 -z = 1
z= -10/3+132/21-1
z=(-210+396-63)/63
z=123/63 --- z solved
x= -5/3
y=44/21
z=123/63